2017
DOI: 10.37341/jkkt.v2i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Mutu Salep Dengan Bahan Aktif Temugiring, Kencur Dan Kunyit

Abstract: Quality Evaluation, Ointments, Kaemferia Galanga, Curcuma Domestica, Curcuma Heynena. Indonesia is a country with very high biodiversity. In the high diversity of the stored potential nutritious plants that can be explored and exploited further. Community began to realize the use of chemicals to cope with life problems, especially health problems, in addition to expensive, can also result in less side effects both for humans. This study used a extract Curcuma domestica, Kaemferia galanga, and Curcuma heynena a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…It may correlate with the concentration of polymer that can make thin gel network (Ardana et al, 2015;Kim et al, 2003). Topical preparation should have adhesion value at more than 4 seconds (Lestari et al, 2017). In table 4, we can see that F2, F3, F4, F5 and F6 fulfilled the requirement of adhesion value, but F6 showed a decrease in adhesion that indicated that F6 are altered after cycling test.…”
Section: Resultsmentioning
confidence: 94%
“…It may correlate with the concentration of polymer that can make thin gel network (Ardana et al, 2015;Kim et al, 2003). Topical preparation should have adhesion value at more than 4 seconds (Lestari et al, 2017). In table 4, we can see that F2, F3, F4, F5 and F6 fulfilled the requirement of adhesion value, but F6 showed a decrease in adhesion that indicated that F6 are altered after cycling test.…”
Section: Resultsmentioning
confidence: 94%
“…Daya lekat sediaan semipadat yang baik adalah lebih dari 1 detik (Ansel, 2008) dan tidak kurang dari 4 detik (Lestari et al, 2017). Semakin lama sediaan krim melekat pada kulit semakin tinggi pula absorbsi obat oleh kulit (Ayu and Oktavianingtyas, 2014).…”
Section: Daya Lekatunclassified
“…kurang dari 4 detik (Lestari et al, 2017). Kriteria respon daya lekat dipilih maximize agar sediaan topikal dapat melekat secara optimum pada kulit.…”
Section: Penentuan Target Responunclassified
“…Pada penelitian didapati bahwa hanya 5 dari 6 kadar yang diusulkan, yang berhasil membentuk massa salep yaitu 5%, 10%, 15%, 20% dan 25% sedangkan kadar 30% tidak terbentuk. Kondisi ini diduga karena pada kadar 30%, kemampuan basis salep untuk mengemulsikan madu kelulut (fase air) dan minyak zaitun (fase minyak) sudah tidak memadai lagi (Lestari, Yunianto, & Winarso, 2017;Naibaho, Yamlean, & Wiyono, 2013;Zulkhairi Amin et al, 2018b).…”
Section: Pengolahan Dan Analisis Dataunclassified